Cinnamate 4-hydroxylase (C4H) genes from leucaena leucocephala: a pulp yielding leguminous tree - Kumar, Santosh; Omer, Sumita; Patel, Krunal; Khan, Bashir Mohammad (Molecular Biology Reports, 2013)
Leucaena leucocephala is a leguminous tree species accounting for one-fourth of raw material supplied to paper and pulp industry in India. Cinnamate 4-Hydroxylase (C4H, EC 1.14.13.11) is the second gene of phenylpropanoid pathway and a member of cytochrome P450 family. There is currently intense interest to alter or modify lignin content of L. leucocephala. Three highly similar C4H alleles of LlC4H1 gene were isolated and characterized. The alleles shared more than 98 % sequence identity at amino acid level to each other. Binding of partial promoter of another C4H gene LlC4H2, to varying amounts of crude nuclear proteins isolated from leaf and stem tissues of L. leucocephala formed two loose and one strong complex, respectively, suggesting that the abundance of proteins that bind with the partial C4H promoter is higher in stem tissue than in leaf tissue. Quantitative Real Time PCR study suggested that among tissues of same age, root tissues had highest level of C4H transcripts. Maximum transcript level was observed in 30 day old root tissue. Among the tissues investigated, C4H activity was highest in 60 day old root tissues. Tissue specific quantitative comparison of lignin from developing seedling stage to 1 year old tree stage indicated that Klason lignin increased in tissues with age.
Keywords: Cinnamate 4-Hydroxylase (C4H); Leucaena leucocephala; lignin; Phenylpropanoid

Probing the active site of cinnamoyl CoA reductase 1 (Ll-CCRH1) from Leucaena leucocephala - Sonawane, Prashant; Patel, Krunal; Vishwakarma, Rishi Kishore; Srivastava, Sameer; Singh, Somesh; Gaikwad, Sushama M.; Khan, Bashir Mohammad (International Journal of Biological Macromolecules, 2013)
Lack of three dimensional crystal structure of cinnamoyl CoA reductase (CCR) limits its detailed active site characterization studies. Putative active site residues involved in the substrate/NADPH binding and catalysis for Leucaena leucocephala CCR (Ll-CCRH1; GenBank: DQ986907) were identified by amino acid sequence alignment and homology modeling. Putative active site residues and proximal H215 were subjected for site directed mutagenesis, and mutated enzymes were expressed, purified and assayed to confirm their functional roles. Mutagenesis of S136, Y170 and K174 showed complete loss of activity, indicating their pivotal roles in catalysis. Mutant S212G exhibited the catalytic efficiencies less than 10% of wild type, showing its indirect involvement in substrate binding or catalysis. R51G, D77G, F30V and I31N double mutants showed significant changes in K-m values, specifying their roles in substrate binding. Finally, chemical modification and substrate protection studies corroborated the presence Ser, Tyr, Lys, Arg and carboxylate group at the active site of Ll-CCRH1. (c) 2013 Elsevier B.V. All rights reserved.
Keywords: Chemical modification; Cinnamoyl CoA reductase 1; Docking simulations; homology modeling; Site directed mutagenesis; Substrate protection

c Squalene synthase gene from medicinal herb bacopa monniera: molecular characterization, differential expression, comparative modeling, and docking studies - Vishwakarma, Rishi K.; Patel, Krunal; Sonawane, Prashant; Kumari, Uma; Singh, Somesh; Ruby; Shakeel Abbassi; Agrawal, Dinesh C.; Tsay, Hsin-Sheng; Khan, Bashir Mohammad (Plant Molecular Biology Reporter, 2015)
The widespread pharmaceutically important triterpenoid saponins are synthesized via isoprenoid pathway. The formation of squalene is the key regulatory point in triterpene biosynthesis, catalyzed by squalene synthase (SQS). The present study deals with the detailed characterization of SQS by molecular, biochemical, and computational means from Bacopa monniera, an immensely important medicinal plant rich in triterpenoid saponin, bacosides. A full-length SQS gene was isolated from B. monniera, characterized as B. monniera squalene synthase (BmSQS) (1242 bp) encoding 414 amino acids. Deduced amino acid sequence of BmSQS showed highly conserved consensus aspartate-rich motifs (DXXXD) and catalytic site residues. Phylogenetic analysis showed that BmSQS belongs to dicot group having closest relationship with Salvia miltiorrhiza. Semiquantitative and real-time PCR studies showed that the BmSQS messenger RNA (mRNA) expression level was higher in vegetative parts (roots) as compared to floral parts. Methyl jasmonate induces the BmSQS mRNA expression in all tissues tested, while salicylic acid, cold, and salt induce much higher expression in roots. Homology modeling and docking simulations of BmSQS showed the pivotal roles of Asp77, Asp81, Asp213, Asp217, and Tyr168 in catalysis.
Keywords: Abiotic stress; Bacopa monniera; Comparative modeling and docking; Differential expression; Isoprenoid pathway; Squalene synthase

In silico ligand binding studies of cyanogenic beta-glucosidase, dhurrinase-2 from Sorghum bicolor - Mahajan, Chavi; Patel, Krunal; Khan, Bashir Mohammad; Rawal, Shuban S. (Journal of Molecular Modeling, 2015)
Dhurrinase, a cyanogenic beta-glucosidase from Sorghum bicolor is the key enzyme responsible for the hydrolysis of dhurrin to produce toxic hydrogen cyanide, as a part of plant defence mechanism. Dhurrinase 1 (SbDhr1) and dhurrinase 2 (SbDhr2), two isozymes have been isolated and characterized from S. bicolor. However, there is no information in the literature about the three dimensional (3D) structure of SbDhr2 and molecular interactions involved between the protein and ligand. In this study, the three dimensional structure of SbDhr2 was built based on homology modeling by using the X-ray crystallographic structure of its close homologue SbDhr1 as the template. The generated 3D model was energy minimized and the quality was validated by Ramachndran plot, various bioinformatic tools and their relevant parameters. Stability, folding-unfolding and flexibility of the modeled SbDhr2 was evaluated on the basis of RMSD, radius of gyration (R-g) and RMSF values respectively, obtained through molecular dynamic (MD) simulation. Further, molecular docking was performed with its natural substrate dhurrin, one substrate analogue, three un-natural substrates, and one inhibitor. Analysis of molecular interactions in the SbDhr2-ligand complexes revealed the key amino acid residues responsible to stabilize the ligands within the binding pocket through non-bonded interactions and some of them were found to be conserved (Glu239, Tyr381, Trp426, Glu454, Trp511). Reasonably broader substrate specificity of SbDhr2 was explained through the wider entrance passage observed in comparison to SbDhr1.
Keywords: beta-Glucosidase; Dhurrinase; Molecular docking; Molecular dynamic simulation; Sorghum bicolor

Insights into the unfolding pathway and identification of thermally sensitive regions of phytase from aspergillus niger by molecular dynamics simulations - Kumar, Kapil; Patel, Krunal; Agrawal, Dinesh C.; Khire, Jayant Malhar (Journal of Molecular Modeling, 2015)
Thermal stability is of great importance in the application of commercial phytases. Phytase A (PhyA) is a monomeric protein comprising twelve alpha-helices and ten beta-sheets. Comparative molecular dynamics (MD) simulations (at 310, 350, 400, and 500 K) revealed that the thermal stability of PhyA from Aspergillus niger (A. niger) is associated with its conformational rigidity. The most thermally sensitive regions were identified as loops 8 (residues 83-106), 10 (161174), 14 (224-230), 17 (306-331), and 24 (442-444), which are present on the surface of the protein. It was observed that solvent-exposed loops denature before or show higher flexibility than buried residues. We observed that PhyA begins to unfold at loops 8 and 14, which further extends to loop 24 at the C-terminus. The intense movement of loop 8 causes the helix H2 and beta-sheet B3 to fluctuate at high temperature. The high flexibility of the H2, H10, and H12 helices at high temperature resulted in complete denaturation. The high mobility of loop 14 easily transfers to the adjacent helices H7, H8, and H9, which fluctuate and partially unfold at high temperature (500 K). It was also observed that the salt bridges Asp110-Lys149, Asp205-Lys277, Asp335-Arg136, Asp416-Arg420, and Glu387-Arg400 are important influences on the structural stability but not the thermostability, as the lengths of these salt bridges did not increase with rising temperature. The salt bridges Glu125-Arg163, Asp299-Arg136, Asp266-Arg219, Asp339-Lys278, Asp335-Arg136, and Asp424-Arg428 are all important for thermostability, as the lengths of these bridges increased dramatically with increasing temperature. Here, for the first time, we have computationally identified the thermolabile regions of PhyA, and this information could be used to engineer novel thermostable phytases. Numerous homologous phytases of fungal as well as bacterial origin are known, and these homologs show high sequence similarity. Our findings could prove useful in attempts to increase the thermostability of homologous phytases via protein engineering.
Keywords: Conformational dynamics; Molecular dynamics simulations; PhytaseA; Structurally weak regions; Thermostability

Functional and conformational transitions of mevalonate diphosphate decarboxylase from Bacopa monniera - Shakeel, Abbassi; Patel, Krunal; Khan, Bashir Mohammad; Bhosale, Siddharth H.; Gaikwad, Sushama M. (International Journal of Biological Macromolecules, 2016)
Functional and conformational transitions of mevalonate diphosphate decarboxylase (MDD), a key enzyme of mevalonate pathway in isoprenoid biosynthesis, from Bacopa monniera (BmMDD), cloned and overexpressed in Escherichia coli were studied under thermal, chemical and pH-mediated denaturation conditions using fluorescence and Circular dichroism spectroscopy. Native BmMDD is a helix dominant structure with 45% helix and 11% sheets and possesses seven tryptophan residues with two residues exposed on surface, three residues partially exposed and two situated in the interior of the protein. Thermal denaturation of BmMDD causes rapid structural transitions at and above 40 degrees C and transient exposure of hydrophobic residues at 50 degrees C, leading to aggregation of the protein. An acid induced molten globule like structure was observed at pH 4, exhibiting altered but compact secondary structure, distorted tertiary structure and exposed hydrophobic residues. The molten globule displayed different response at higher temperature and similar response to chemical denaturation as compared to the native protein. The surface tryptophans have predominantly positively charged amino acids around them, as indicated by higher K-SV for IC as compared to that for CsCl. The native enzyme displayed two different lifetimes, vi (1.203 +/- 0.036 ns) and tau 2 (3.473 +/- 0.12 ns) indicating two populations of tryptophan. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Aggregation; CD spectroscopy; Fluorescence quenching; Mevalonate diphosphate decarboxylase; Unfolding